A concise introduction to econometrics - Franses, P.H. (Cambridge University Press, 2012)
In this short and very practical introduction to econometrics Philip Hans Franses guides the reader through the essential concepts of econometrics. Central to the book are practical questions in various economic disciplines, which can be answered using econometric methods and models. The book focuses on a limited number of the essential, most widely used methods, before going on to review the basics of econometrics. The book ends with a number of case studies drawn from recent empirical work to provide an intuitive illustration of what econometricians do when faced with practical questions. Throughout the book Franses emphasizes the importance of specification, evaluation, and implementation of models appropriate to the data.